Transkei grasslands : recent phenomenon or ancient? - Foord, John (Department of Biological Sciences, 2017)
Acocks (1953) suggested that Transkei was once covered in Forest and Scrub-Forest and has possibly been transformed by the Iron Age Farmers to grasslands. Feely (1985) suggested that the grasslands are ancient. I therefore used C isotope analysis to reveal whether there has been any change in the dominant vegetation during the Iron Age period. We measured the δ¹³C value of the soil organic matter taken at various depths These were taken from selected sites throughout Transkei that represented the grasslands, forests and grasslands suspected of once being forest or scrub-forest. The results show that the vegetation has remained stable. Those area that are presently covered in grasslands have remained grasslands for the time period represented by the depth of the samples taken. There is however a small shift in the forest and grassland sites to a lower isotopic value either as a result of changing vegetation or changes in the atmospheric [O₂]. There is also archaeological, ecological and historical evidence supporting these results. There is evidence of settlements scattered along the coast and in river valleys during the Early Iron Age (AD 300 to AD 1000). The earliest evidence of settlements during the Late Iron Age dates to AD 1400. The impact of the farmers appears to be localised and the vegetation type appears to have remained constant although impacted on.